Entrepreneurial orientation, marketing capability, and adaptive capability: Drivers of business performance - Vedy, Nabila Kharimah; Vedy, Hanifah Syahirah; Rahayu, Sri (Goodwood Publishing, 2025)
Purpose: The purpose of this research is to address the capabilities possessed by individuals to encourage entrepreneurial orientation towards business performance in turbulent environments, which involves marketing capability and adaptive capability. Method: This study employed a qualitative research design that uses secondary data derived from previous studies that have theoretical relevance. Results: The results of the analysis revealed that improving business performance needs to be supported by individual capabilities such as entrepreneurial orientation, marketing capabilities, and adaptive capabilities in turbulent environments. It is believed that entrepreneurial orientation is a strategy that is still relevant to be used to encourage business performance either directly or supported by marketing capabilities and adaptive capabilities. Conclusions: It can be concluded that entrepreneurial orientation, marketing capability, and adaptive capability are important factors in improving business performance. Limitations: This research is still a conceptual paper. This causes this research to be suboptimal because there is no data being optimized to support this research. Therefore, this study only obtained data from previous research. Contribution: This study contributes to a more comprehensive knowledge of how entrepreneurial orientation, marketing capabilities, and adaptive capabilities together influence business performance. It provides practical assistance to business actors and policymakers while providing a foundation for future academic research.